Developing a Vital Signal Detection Electrode for Fabric Substrate Using a High-Performance Conductive Carbon-Based Ink - K. Chansaengsri; B. Tunhoo; K. Onlaor; T. Thiwawong (IEEE Open Journal of Engineering in Medicine and Biology)
Merging electrophysiology signal monitoring technology with wearable devices offers interesting future health care options. This study presented carbon-based screen-printing inks produced by mixing a graphite composite with a polymer emulsion to bind with flexible fabric substrates and tested with 10,000 bending cycles. The prepared carbon-based ink performed well for electrical conduction and vital signal response. Adding calcium carbonate resulted in a microstructure of graphite that decreased the electrical sheet resistance and resistance to 11.61 Ω/◻ and 0.127 Ω. The signal-to-noise ratio of the electrocardiogram (ECG) was 31.02 dB with built-in front-end powering noise filtration. Noninvasive blood pressure (NIBP) was achieved by bio-impedance measurement and showed outstanding systolic and diastolic pressure values with a correlation coefficient of 0.799, and exhibited a similar interval time to define the same precise heart rate. The ECG data from the prepared electrode were applied to the machine learning models. The Random Forest (RF) model exhibited the optimized prediction value, with an F1 score of 99.9%. Equipment made from carbon screen-printing inks showed potential for health care monitoring with no excessive pressure, dry processing, and repeatability as a flexible wearable bio-electronic device.